Profil Numerasi Siswa Ditinjau dari Tingkat Kecemasan Matematika - Alvina Salsabila; Nina Rinda Prihartiwi (MATHEdunesa, 2026)
Numeracy is an important competency in mathematics learning related to students' ability to use mathematical concepts and reasoning in everyday life contexts. In the National Assessment policy, numeracy is measured through the Minimum Competency Assessment (AKM), which emphasizes contextual problem solving. However, students' numeracy is not only influenced by mastery of mathematical concepts, but also by affective factors, one of which is mathematics anxiety. Mathematics anxiety can affect students' focus, self-confidence, and thought processes. This study aims to describe students' numeracy in terms of low, medium, and high levels of mathematics anxiety. This study used a qualitative approach. The research subjects consisted of three junior high school students, each representing low, medium, and high levels of mathematics anxiety. Data collection techniques included completing a mathematics anxiety questionnaire and a numeracy test equivalent to AKM, interviews, observations, and field notes. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results showed that students with low levels of mathematics anxiety had good numeracy skills across all numeracy indicators. Students with moderate levels of math anxiety demonstrated adequate but inconsistent numeracy skills, particularly in accuracy and mathematical justification. Meanwhile, students with high levels of math anxiety demonstrated low numeracy skills, characterized by difficulty understanding the context of AKM questions, processing information, and drawing appropriate conclusions.